2007
DOI: 10.1186/gb-2007-8-6-r118
|View full text |Cite
|
Sign up to set email alerts
|

Fast-evolving noncoding sequences in the human genome

Abstract: Fast-evolving non-coding sequences

Over 1,300 conserved non-coding sequences were identified that appear to have undergone dramatic human-specific changes in selective pressures; these are enriched in recent segmental duplications, suggesting a recent change in selective constraint following duplication.

Abstract Background: Gene regulation is considered one of the driving forces of evolution. Although protein-coding DNA sequences and RNA genes have been subject to recent evolutionary events in the huma…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
175
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(187 citation statements)
references
References 38 publications
(44 reference statements)
6
175
1
1
Order By: Relevance
“…This field has introduced new datasets to test disease origins in humans, including Human Accelerated Regions (HARs) and Neanderthal Selective Sweep (NSS) scores (17,18). HARs are genomic regions that are highly conserved in non-human species, but have undergone rapid sequence change in the human lineage (19)(20)(21)(22)(23). Xu et al (17) showed that genes near HARs are enriched for association with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…This field has introduced new datasets to test disease origins in humans, including Human Accelerated Regions (HARs) and Neanderthal Selective Sweep (NSS) scores (17,18). HARs are genomic regions that are highly conserved in non-human species, but have undergone rapid sequence change in the human lineage (19)(20)(21)(22)(23). Xu et al (17) showed that genes near HARs are enriched for association with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Instances of human-specific acceleration of functional non-coding regions, for example, have been associated to adaptive evolution (Pollard et al 2006;Prabhakar et al 2006;Bird et al 2007;Kim & Pritchard 2007), but a substantial fraction of these episodes were eventually found to be consistent with increased evolutionary rates owing to gBGC (Galtier & Duret 2007;Duret & Galtier 2009b). Most phylogenetic tests of positive selection on protein-coding genes use the ratio of non-synonymous (d N ) to synonymous (d S ) substitution rates.…”
Section: Introductionmentioning
confidence: 99%
“…Although HAR sequences showed enriched overlap with the identified brain regulatory elements, they were not more prevalent at the human-specific enhancers. In another study by Boyd et al, a previous identified accelerated non-coding genetic locus [78] was implicated as a Human-specific enhancer, termed Human-Accelerated Regulatory Enhancer 5 (HARE5) of the FZD8 gene [79]. This is a receptor in the Wnt pathway involved in neural progenitor proliferation and implicated in brain development and size.…”
Section: Sequence Redundancy In Enhancersmentioning
confidence: 99%